Revision of the Genus Psectrotarsia Dognin, 1907 (Lepidoptera: Noctuidae: Heliothinae) - Pogue, Michael G. (Zootaxa, 2007)
Based on characters of the male and female genitalia, the genus Erythroecia Hampson, 1910 is considered a new syn- onym of Psectrotarsia Dognin, 1907. Psectrotarsia contains five species: P. flava Dognin (type species); P. suavis (H. Edwards), new combination; P. hebardi (Skinner), new combination; P. euposis (Dyar), new combination and revised status; and P. rhodophora (Hampson), new combination. Each species is redescribed and illustrated. Copitarsia fuscirena (Hampson), new combination, and C. tamsi (Giacomelli), new combination, are transferred from Psectrotarsia to Copitarsia Hampson, 1906. Psectrotarsia ranges from the northeastern, midwestern, and southwestern United States to Guatemala.